Investigational Drugs for the Treatment of Depression (Part 1): Monoaminergic, Orexinergic, GABA-Ergic, and Anti-Inflammatory Agents - Vasiliu, Octavian (Frontiers in Pharmacology, 2022)
Therapeutic management of depression has currently important limitations, and its low efficacy is reflected in high rates of non-response even after multiple trials of antidepressants. Almost two-thirds of the patients diagnosed with major depression who received a 4-6 weeks trial of antidepressant could not reach remission, and more than 30% of these patients are considered treatment-resistant. In bipolar depression, the situation is also discouraging if we analyze the high suicide rate, the risk for the treatment-emergent affective switch when antidepressants are added, the high rate of treatment resistance (up to 25%), and the severe functional impairments associated with these episodes. Therefore, new therapeutic agents are needed, as well as new pathogenetic models for depression. The vast majority of the currently approved antidepressants are based on the monoamine hypothesis, although new drugs exploiting different neurotransmitter pathways have been recently approved by FDA. Brexanolone, an allopregnanolone analog, is an example of such new antidepressants, and its approval for post-partum depression inspired the search for a new generation of neurosteroids and GABA-ergic modulators, with an easier way of administration and superior tolerability profile. Orexin receptors antagonists are also extensively studied for different psychiatric disorders, depression included, in phase II trials. Antiinflammatory drugs, both cyclo-oxygenase 2 inhibitors and biological therapy, are investigated in patients with depressive disorders based on the proven correlation between inflammation and mood disorders in preclinical and clinical studies. Also, a new generation of monoamine-based investigational drugs is explored, ranging from triple reuptake inhibitors to atypical antipsychotics, in patients with major depression. In conclusion, there is hope for new treatments in uni- and bipolar depression, as it became clear, after almost 7 decades, that new pathogenetic pathways should be targeted in order to increase these patients’ response rate.